Preparation and Characterization of Ionic Liquild Modified Montmorillonite and its Application in Poly(propylene)/Montmorillonite Nanocomposites - Wang, L.M. (Asian Journal of Chemistry, 2011)
Montmorillonite was organically modified with one kind of ionic liquild. Resulted organical modified montmorillonite was used to prepare a novel Ziegler-Natta/montmorillonite compound catalyst. Poly(propylene)/montmorillonite nanocomposites were synthesized with this argillaceous composite catalyst. Fourier transform infrared, wide angle X-ray diffraction (XRD) and thermogravimetric analysis (TGA) revealed that the 1-hexadecaneimidazolium cation was loaded in the galleries of the obtained ionic liquid montmorillonite. Thermogravimetric analysis result showed the thermal stability of ionic liquid montmorillonite was superior to montmorillonite. XRD patterns indicated that the d spacing of ionic liquid montmorillonite layers increased to 3.14 nm. XRD patterns of poly(propylene)/montmorillonite nanocomposites showed that montmorillonite layers was dispersed in poly(propylene) matrix by nanometer size and that a- phase crystallite was the main crystallite of poly(propylene) in poly(propylene)/montmorillonite nanocomposites, no b-phase and g-phase crystallite were observed in XRD patterns of poly(propylene)/montmorillonite nanocomposites.